Safety of coffee production as the main competitive advantage of the company in the market - Vorobiov, Kostiantyn; Hurzhii, Natalia; Lysenko, Maryna (Management and Entrepreneurship: Trends of Development, 2019)
The relevance of implementing the principles of product safety management caused by the necessity to implement this standard by the Ukrainian enterprises while forming the image of a safe food producer, thereby expressing a serious attitude to the opinion and health of consumers. An equally important effect of the implementation of this standard is the investment attractiveness of the company and the ability to enter the foreign market. Thus, Ukrainian products will be in demand by consumers in the foreign market due to decent quality and affordable prices. Analysis of the prospects for the implementation of the HACCP standard will allow the company to interest the consumer in the purchase of coffee products, reduce the cost of its production, expand its product portfolio and increase distribution channels. The article aims to study the benefits for the company from the application of HACCP, to characterize the process of its implementation and to provide a typical example of real deviations in the designed enterprise models. Methodology: during the study, a qualitative analysis of the existing DSTU ISO 22000: 2007 standard was carried out, as well as the analysis of the existing deviations of coffee production. The scientific significance of the study lies in the fact that, based on the conducted research results, it is possible to develop typical processes for the accelerated implementation of HACCP standards, which in turn will accelerate the intensity of its high-quality implementation. The value of the research is that, based on the implementation of standards for the management of safe coffee products, the consumer receives a quality product, while the state obtains a certified manufacturer and potential exporter.JEL Classification: L15, K13, J28.